Correction to: Dodging bullets: The heterogeneous effect of political violence on greenfield FDI - Witte, Caroline T; Burger, Martijn J; Ianchovichina, Elena I; Pennings, Enrico (Journal of International Business Studies, 2019)
Owing to a production error, the coefficients of the BRD (ln) * localized and Greenfield FDI variables were not correctly displayed in the even columns of Table 2 in the original article.